A new informal group in Chusquea subg. Swallenochloa (Poaceae: Bambusoideae: Bambuseae) and emended descriptions for the Mexican endemics C. enigmatica and C. septentrionalis - Ruiz-Sanchez, Eduardo; Castro-Castro, Arturo; Clark, Lynn G. (Phytotaxa, 2022)
The Neotropical genus Chusquea, with 197 described species, is the most diverse genus of bamboo worldwide. Mexico has 24 species of Chusquea representing two of the five subgenera: Chusquea subg. Chusquea and C. subg. Swallenochloa. Nineteen species belong to subg. Chusquea and just five to subg. Swallenochloa. Chusquea enigmatica, classified in subg. Chusquea, and C. septentrionalis, classified in subg. Swallenochloa, were both described from vegetative material. Based on recent  fieldwork in the Mexican states of Durango, Hidalgo, San Luis Potosí, and Sinaloa, we found new populations of C. enigmatica outside of the original localities in Hidalgo and San Luis Potosí. In San Luis Potosí, we found one population was flowering. For C. septentrionalis we found a new locality in Durango in which all individuals in the population were flowering, and a new population from Sinaloa. Here, we present emended morphological descriptions, illustrations, comparative tables, and a distribution map for C. enigmatica and C. septentrionalis. The reproductive characters of C. enigmatica are compared to C. lanceolata, whereas those of C. septentrionalis are compared to C. bilimekii and C. perotensis. We transfer C. enigmatica and C. gibcooperi, which share an unusual branching pattern involving intra- and extravaginal branching on the same plant, to subg. Swallenochloa. We also establish the C. lanceolata informal group within this subgenus to include C. enigmatica, C. gibcooperi and C. lanceolata, which share leptomorph rhizomes.